Case Report: Nirogacestat therapy induces rapid response in a patient with refractory, life-threatening desmoid tumor - Harrer, Dennis Christoph; Herrmann, Markus; Vogelhuber, Martin; Geis, Sebastian; Mahr, Daniel; Niethard, Maya; Keil, Felix; Napodano, Gerardo; Herr, Wolfgang; Grube, Matthias (Frontiers in Oncology, 2025)
BackgroundDesmoid tumor (DT) is a rare soft tissue neoplasm characterized by locally aggressive infiltration into adjacent tissues with few established treatment regimens. So far, the evidence-based therapeutic arsenal for DT has comprised surgery, locoregional therapy, tyrosine kinase inhibitor treatment, and chemotherapy. The γ-secretase inhibitor nirogacestat was approved by the FDA in 2023 and, in 2025, received European authorization as the first and only agent for treatment of progressive DT requiring systemic therapy predicated on positive results from an international phase 3 clinical trial.MethodsSingle case study and review of the literature.Case presentationWe report on a 29-year-old patient with a recurrent DT located below the right mastoid process with extensive infiltration into cervical tissue and compression of the right internal jugular vein. Following early relapse to surgery, the patient sequentially failed treatment with pegylated liposomal doxorubicin (PLD), sorafenib, and a combination of doxorubicin and dacarbazine. Against the backdrop of life-threatening circumstances due to pending infiltration of the right carotid artery, the patient was subjected to nirogacestat treatment as part of a compassionate use program. Upon four months of nirogacestat treatment, MRI-imaging revealed a sizable regression of the DT, substantially decreasing the danger of carotid artery infiltration. Currently, the patient continues nirogacestat treatment, and no severe side effects were observed.ConclusionAlbeit rarely lethal in general, DT can exert life-threatening danger by local infiltration into vital tissue, such as blood vessels. The presented case highlights the novel γ-secretase inhibitor nirogacestat as a highly effective therapy preventing infiltration of the right carotid artery by a remarkably refractory DT.